2011
DOI: 10.1117/1.3533320
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative evaluation of revascularization effect on ischemic muscle hemodynamics using near-infrared diffuse optical spectroscopies

Abstract: Abstract. Arterial revascularization in patients with peripheral arterial disease (PAD) reestablishes large arterial blood supply to the ischemic muscles in lower extremities via bypass grafts or percutaneous transluminal angioplasty (PTA). Currently no gold standard is available for assessment of revascularization effects in lower extremity muscles. This study tests a novel near-infrared diffuse correlation spectroscopy flow-oximeter for monitoring of blood flow and oxygenation changes in medial gastrocnemius… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 62 publications
(92 reference statements)
2
58
0
Order By: Relevance
“…3) and DCT (Fig. 4) measurements in different applications (Huang et al , 2015c; Durduran et al , 2005; Yu et al , 2011; Shang et al , 2011b; Huang et al , 2015b) (see Section 3 ). These probes are connected to the DCS/DCT instruments (Fig.…”
Section: Dcs/dct Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) and DCT (Fig. 4) measurements in different applications (Huang et al , 2015c; Durduran et al , 2005; Yu et al , 2011; Shang et al , 2011b; Huang et al , 2015b) (see Section 3 ). These probes are connected to the DCS/DCT instruments (Fig.…”
Section: Dcs/dct Methodsmentioning
confidence: 99%
“…A few studies have been reported using DCS to investigate the impacts of surgical interventions on skeletal muscle diseases (Yu et al , 2011; Huang et al , 2015c). For muscular revascularization, ultrasound Doppler is routinely used in surgical rooms to test post-surgical reperfusion in large vessels.…”
Section: Clinical Application Examplesmentioning
confidence: 99%
“…[25][26][27] DCS can be easily and continually applied at the bedside in clinical rooms. [28][29][30][31][32][33][34] 35 and has been used less in the "cancer" context than in other scenarios such as brain and muscle. Therefore, a review of potential for cancer applications of DCS is valuable at this time for both optical and cancer communities.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] The blood flow index (BFI) measured by DCS has been validated by arterial spin-labeled magnetic resonance imaging, 11 Doppler ultrasound, 12,13 Xenon computed tomography, 14 and laser Doppler flowmetry. 15,16 Further, DCS systems have been used to monitor blood flow changes in clinical applications associated with brain, 13,14,17 skeletal muscle, 11,18,19 and tumors. 10,[20][21][22][23] When taken together, DCS and DOSI can provide a noninvasive measurement of the metabolic rate of oxygen consumption in tissue, and indeed, several studies have shown that the combination of DOSI and DCS techniques in breast lesion characterization provides a better understanding of tumor physiology and metabolism and may enhance treatment monitoring in the presurgical setting.…”
Section: Introductionmentioning
confidence: 99%